Review of the design and condition monitoring of overhead power distribution conductors - Jayathilake, Shiroshi; Rajeev, Pathmanathan; Gad, Emad (Journal of Civil Engineering and Management, 2025)
Bushfires, also known as wildfires in some parts of the world, is a major hazard with significant risks to communities and the environment. Such fires can initiate from a number of sources including lightning. However, one of the possibilities for initiating bushfires is faults in the power system. Faults in conductors can happen overtime and monitoring is essential for effective maintenance and avoiding unnecessary power failures. Simultaneously, assessing conductor reliability is critical for powerline asset management. This paper comprehensively reviews conductor design and monitoring in the distribution network. Various conductor types and applications are described using population statistics from the Australian power distribution network. Furthermore, the design approach in the Australian Standard is briefly explained and further design methodologies are assessed, emphasizing the progress of innovative approaches. Additionally, potential conductor failure modes in Australia’s distribution network are identified. The paper also outlines different condition assessment methods and explores their advancement. Finally, possible models for evaluating conductor reliability are examined, underscoring their benefits in accounting for weather-induced impacts.